A revision of the genus Atelecrinus PH Carpenter (Echinodermata: Crinoidea) - Messing, Charles G. (Zootaxa, 2013)
The unusual bathyal comatulid crinoid genus Atelecrinus is widespread in the Atlantic and tropical Pacific Oceans and currently includes three recognized species. A re-assessment based on examination of new and existing specimens re-quires establishment of two new genera and five new species, and returns three junior synonyms to species-level status. Paratelecrinus is erected to accommodate Atelecrinus wyvilli PH Carpenter, A. conifer AH Clark, A. cubensis PH Carpen-ter, P. orthotriremis, new species, P. amenouzume new species, P. laticonulus new species and P. telo new species. Ade-latelecrinus is erected to accommodate Atelecrinus sulcatus AH Clark and Adelatelecrinus vallatus new species. Atelecrinus retains A. balanoides PH Carpenter and A. helgae AH Clark, which restricts the genus to the Atlantic. In both Paratelecrinus and Adelatelecrinus, the basals articulate with the centrodorsal via ligament bundles anchored in deep ring-like interradial pits that project into the centrodorsal cavity, whereas in Atelecrinus the centrodorsal rim has shallow inter-radial concavities and attaches to the basals via a tight junction with no obvious ligament bundles. The spoon-shaped ab-oral fossa in the basals of Paratelecrinus appears to be unique among articulate crinoids and differs from the smooth fossa found in both Atelecrinus and Adelatelecrinus. New material extends the range of the family to the Indian Ocean. A few species are now known from enough specimens to identify some ontogenetic and distributional variations. Proximal ray morphology varies substantially with size in P. cubensis and P. orthotriremis. A. balanoides generally occurs in deeper water in the Lesser Antilles than in the Bahamas and Strait of Florida, while P. orthotriremis occurs in shallower water in the Lesser Antilles and deeper in the Bahamas.